Corpus luteum development and efficacy of GnRH treatment in non-infectious cyclic non-breeder animals - MARKANDEYA, N M; PATIL, A D (The Indian Journal of Animal Sciences, 2011)
The present study revealed that GnRH treatment in noninfectious cyclic non-breeder cases @ l05mg intramuscularly during first phase of oesturs is effective in 83.33% cows with 1.44 services/conception and in 81.81% buffaloes with 1.33 services/conceptions. GnRH treatment, only if succeeds in better development of corpora lutea of grade III or IV size, results in conceptions in non- infectious repeat breeder animals.Â